Analisis Strategi Guru Dalam Meningkatkan Motivasi Belajar Siswa Pada Pembelajaran Matematika Kelas V SDN 2 Badrain - Fausi, Fausi; Darmiany, Darmiany; Wahyuningsih, Baiq Yuni (Lambda: Jurnal Ilmiah Pendidikan MIPA dan Aplikasinya, 2025)
This study aims to describe the strategies used by teachers in increasing student learning motivation in mathematics learning and to determine the factors that influence teachers in increasing student learning motivation at SDN 2 Badrain. The type of research used is descriptive qualitative research. Data collection techniques using observation, interviews, and documentation methods. The research instrument uses observation and interviews. As well as, data analysis techniques use data collection, data condensation, data presentation, and drawing conclusions. The results of this study indicate that : 1. Teacher strategies in increasing student learning motivation in Mathematics learning at SDN 2 Badrain are through several efforts that have been implemented by teachers, including: physical and mental readiness, increasing concentration, increasing interest and motivation, using learning strategies, various learning methods, giving appreciation (rewards)/punishments, and learning evaluation. 2. The supporting factors in increasing student learning motivation include support from the school environment, availability of infrastructure, teacher flexibility, and student enthusiasm supported by parents and a positive social environment. However, there are also inhibiting factors such as lack of teacher preparation, low student concern, a less conducive classroom atmosphere, and negative student perceptions of mathematics.